Grammatical features of translation of agrarian literature from the German to the Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Grammatical features of translation of agricultural literature from the German to the Ukrainian are considered. Translator which translates science and technology texts, particularly agricultural literature should understand the text so he can properly recreate it in another language. When translating texts from one language to another there are translation difficulties associated with syntactic differences between the systems of initial and target languages. So translators have to solve these problems, given attention to the grammatical peculiarities of translation and using translation transformation. It is stated out that differences in the construction of sentences in German and Ukrainian languages changes the word order in the translation from German into Ukrainian. One of the grammatical peculiarities of Ukrainian translation of German agrarian texts is due to differences in the use of active and passive voice. It is identified that the ability to reduce the German common ingredient in compound nouns, carried out in order to save linguistic resources and avoiding reduplication has no analogue in the Ukrainian language. Therefore Ukrainian translation contains the full equivalent of these concepts. The necessity of grammatical transformations is substantiated. It was determined that grammatical differences between the German and Ukrainian languages make it necessary to use when translating texts from German agrarian texts in Ukrainian such methods: changing the word order in a sentence, adding the words, transformation of a simple sentence in complex, replacement of speech parts.
Keywords: agrarian literature; translation; word order; grammatical transformation